PENGARUH BEBAN PAJAK, INTANGIBLE ASSETS, PROFITABILITAS, TUNNELING INCENTIVE, DAN MEKANISME BONUS TERHADAP TRANSFER PRICING (Studi Empiris Pada Perusahaan Manufaktur Yang Listing di Bursa Efek Indonesia Periode tahun 2014-2016) - Anisyah, Fitri; Ratnawati, Vince; Natariasari, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this study was to examine the effect the of tax expense, intangible assets, profitability, tunneling incentive, and bonus mechanism to transfer pricing at manufacturing company which are listed on Indonesia Stock Exchange 2014-2016. The samples used in this study were 36 manufacturing companies. Sampling method in this study obtained by using purposive sampling method. Hypothesis test in this study use logistic regression with t test and coefficient of determination tested by using SPSS 21. The result of this study shows that tax expense, profitabilitity, tunneling incentive has an effect on transfer pricing. While also, intangible assets and bonus mechanics didn’t effect the transfer pricing.Keywords: Tax Expense, Intangibel Assets, Profitability, Tunneling Incentive, Bonus Mechanics, Transfer Pricing.